Literasi Aplikasi Akuntansi Pada Kelompok Ibu Rumah Tangga Di Kelurahan Nambo, Sulawesi Tenggara - Hasbudin; Intihanah; Emillia Nurdin; Januri; Muhammad Nanang; Muhammad Rajab Buruto; Nasruddin; Nirmalasari N.; Sitti Rahmiatin; Upik Sri Rahayu; Wa Ode Suherni (Senarai Kearifan Lokal Akuntansi: Jurnal Pengabdian Masyarakat, 2026)
AbstractThe group of housewives engaged in MSMEs in Nambo Village holds significant economic potential following the development of Nambo Beach tourism, yet they still record finances manually, mix business and personal finances, and have low digital accounting literacy. The aim of the community service activity is to improve the ability to maintain simple bookkeeping records using Microsoft Excel through the SIMUDA UMKM template. The community method uses Participatory Action Research comprising preparation, implementation, and monitoring and evaluation. The activity was actively attended by 24 participants who completed the entire program, with partners becoming able to independently prepare simple financial records using the template's automatic calculation features. This generated social impact through greater awareness of financial recording; economic impact through improved efficiency supporting business decisions and credit access; and institutional impact through strengthened partnerships between higher education and village government, overall enhancing accounting technology literacy and economic empowerment among housewives engaged.